2E.001 Measuring the effectiveness of prevention of family violence in a regional setting. (14th March 2021) - Robinson, Margie; Greville, Heath; Woods, John; Nattabi, Barbara; Moran, Monica; Fisher, Colleen; Thompson, Sandra; Martin, Karen
Abstract : Background: Rates of family and gender-based violence (FV) are high, particularly in rural and remote areas in Australia. The City of Greater Geraldton, a local government area in the Midwest region of Western Australia, has developed a FV primary prevention strategic action plan. Local data are needed to measure the impact of community based prevention efforts. Our research aim was to develop a tool to measure community attitudes and experiences of FV in order to assess the effectiveness of efforts to change attitudes and reduce violence over time. Methods: A working group developed the Local Community Attitudes and Exposure to Violence Survey (LCAEVS), based primarily upon the National Community Attitudes Survey (NCAS), which is periodically undertaken by Australia's National Research Organisation for Women's Safety (ANROWS). Questions from all relevant domains in the NCAS were included, with prioritisation of items likely to be sensitive to change over time. The survey was shortened to reduce respondent burden. Results: Geraldton respondents showed misunderstandings about the key drivers and the gendered pattern of FV, while some local attitudes were less supportive of gender equality than those documented in the national survey. Conclusions: Approaches adopted to distribute the survey, the response rate and demographics of the population who completed it, and comparison of responses of Geraldton residents with those in the NCAS will be discussed. Learning Outcomes: It is feasible to administer a shorter survey based on the NCAS, to measure particular attitudes on which to focus violence prevention education for a regional population.